Indigenization of Knowledge Organization at the Xwi7xwa Library - Ann M. Doyle; Kimberley Lawson; Sarah Dupont (Tu shu zi xun xue kan, 2015)
This paper examines the Indigenization of knowledge organization within library and information studies through conceptual analysis and a descriptive case study of an Aboriginal academic library, the Xwi7xwa Library at the University of British Columbia, Canada. We begin by locating the library in place and time, review its historical development in the context of Indigenous education in Canada and describe the evolution of its unique Indigenous classification scheme and related Indigenous subject headings. This place-based analysis leads to a particular articulation of Indigenization and a conceptual framework for Indigenization of knowledge organization at the Xwi7xwa Library, which guide the practice of knowledge organization design and modes of mobilization at this particular Aboriginal library. The conceptual framework rests on two basic assumptions: firstly, that collection development is curatorial in nature and is the seminal step in library knowledge organization, and, secondly, that the Indigenized knowledge organization system is critical to effective Indigenous information and instructional services, programming and research at the Library. The final section presents future possibilities for the Indigenization of knowledge organization through convergences and collaborations with emerging networks of Indigenous scholars and Indigenous communities of knowledge within the context of new technologies.